A Review on Designand Control Methods of Modular Multilevel Converter - Ramya G; Ramaprabha R (Institute of Advanced Engineering and Science, 2016)
Modular multilevel converters (MMC) are an emerging voltage source converter topology suitable for many applications. Due to abundant utilization of HVDC power transmission, the modular multilevel converter has become popular converter type to be used in high voltage applications. Other applications include interfacing renewable energy power sources to the grid and motor drives. Modular multilevel converters are beneficial for high voltage and high power motor drives because of the properties of this converter topology, such as, low distortion, high efficiency, etc. For the past few years significant research has been carried out to address the technical challenges associated with operation and voltage balancing of MMC. In this paper, a detailed technical review on the control strategies is presented for ready reference.